Comparison of in situ hybridization and monoclonal antibodies for early detection of cytomegalovirus in cell culture. - McClintock, J T (1989)
The abilities of each of four diagnostic tests--direct fluorescent monoclonal antibody (direct FA) staining, indirect fluorescent monoclonal antibody (indirect FA) staining, in situ hybridization with biotinylated DNA probes, and in situ hybridization with DNA probes directly linked to enzymatically active horseradish peroxidase-to detect cytomegalovirus soon after culture were compared. Only the indirect FA test and the in situ hybridization method with directly linked HRP-DNA probes provided consistent and reliable cytomegalovirus detection as early as 15 h postinfection.